Development of single-nucleotide polymorphism markers of salinity tolerance for Tunisian durum wheat using RNA sequencing. (2nd January 2021) - Kim, Sang Heon; Kim, Dae Yeon; Yacoubi, Inés; Seo, Yong Weon
ABSTRACT: Salinity stress is a critical abiotic stress that reduces crop productivity. Durum wheat ( Triticum turgidum ssp. durum ) is an essential cereal in Tunisia, a country threatened by salinity stress. In this study, 26 accessions of Tunisian durum wheat were subjected to salinity stress induced by 500 mM NaCl, and their salinity tolerance was evaluated by examining phenotypic parameters and calculating the salinity tolerance trait index and salinity tolerance index. Furthermore, two Tunisian durum wheat cultivars, namely 'Om Rabia' (salinity-tolerant) and 'Mahmoudi' (salinity-susceptible), were subjected to RNA sequencing (RNA-Seq) analysis, and single-nucleotide polymorphisms (SNPs) were detected from the RNA-Seq data of these two cultivars. The impacts of all SNP variants on genes were predicted, and 157 candidate SNP primer pairs were designed preferentially using high-impact transcripts. Following confirmation using polymerase chain reaction (PCR) analysis of data from 'Om Rabia' and 'Mahmoudi', 17 SNP markers were developed and applied to assess the remaining 26 Tunisian durum wheat lines. Three developed SNP markers ( KUCMB_TRIDC7AG078450.6_12, KUCMB_TRIDC2BG061830.1_05, and KUCMB_TRIDC2BG061830.1_08 ) showed PCR bands only in salinity-tolerant lines but not in moderately tolerant or susceptible lines. Therefore, the developed SNP markers may be used to screen the salinity tolerance of various durum wheat accessions.